Tailored Buckling Microlattices as Reusable Light‐Weight Shock Absorbers. Issue 28 (9th May 2016) - Frenzel, Tobias; Findeisen, Claudio; Kadic, Muamer; Gumbsch, Peter; Wegener, Martin
Abstract : Structures and materials absorbing mechanical (shock) energy commonly exploit either viscoelasticity or destructive modifications. Based on a class of uniaxial light‐weight geometrically nonlinear mechanical microlattices and using buckling of inner elements, either a sequence of snap‐ins followed by irreversible hysteretic – yet repeatable – self‐recovery or multistability is achieved, enabling programmable behavior. Proof‐of‐principle experiments on three‐dimensional polymer microstructures are presented.